Novos dados sobre o megalitismo de Mora: a Anta do Pequito Velho (Mora, Portugal) - Rocha, Leonor (2019)
Mora's megalithism was inventoried and mostly excavated in the first half of the 19th century. XX, by Vergílio Correia and Manuel Heleno, who collected thousands of pieces, currently deposited in the National Archaeological Museum in Lisbon. At the end of 2016, José Lopes Aleixo Cravidão (owner of Monte do Pequito Velho) donated a set of twelve pieces collected in a megalithic monument on his property, destroyed by the construction of a road. It is presented the study of this collection that constitutes an important contribution to the knowledge of funerary rituals in this region.